PERAN IRA ALAWE SO HALOWO DI GEREJA ANGOWULOA FAAWOSA KHO YESU (AFY) - Lawolo, Mey Daman; Buaya, Nur Hayati (Jurnal Teologi RAI, 2024)
Every church denomination has a distinctive feature that colors it. Especially in the AFY Church, Ira Alawe So Halöwö is a striking characteristic because it is not found in other church denominations. Their existence in the AFY church is also recognized based on the decision of the AFY Synod Assembly by stipulating that Ira Alawe So Halöwö always wears a veil (a piece of white cloth) when worshiping and praying. In this paper, the author attempts to explain the phenomenon and its benefits for the AFY church. To explain this phenomenon, the author uses a descriptive qualitative research method that directs the author to explore and present data related to the research topic through interviews and review of related literature. Thus, this research can be concluded that Ira Alawe So Halöwö plays an important role in the ministry of AFY Church as a Prayer Team that must receive guidance for the progress of their ministry.